Diamond for antifouling applications: A review. (30th August 2022) - Deng, Zejun; Zhu, Ruitong; Ma, Li; Zhou, Kechao; Yu, Zhiming; Wei, Qiuping
Abstract: Conventional electrode materials (e.g., metallic electrodes or metal oxides, glassy carbon and carbon fiber electrodes) usually encounter severe surface fouling during electrochemical measurements, particularly for the determination of those fouling agents (e.g., dopamine, amino acids, proteins, drug molecules), leading to the attenuation of the response signal. Diamond electrode materials exhibit exceptional electrochemical properties, including not only the wide potential window for water stability, low background current, excellent electrochemical stability but also exceptional antifouling properties. In the case of conductive diamond electrode materials, particularly for the boron-doped diamond electrode (BDDE), the fouling process can be significantly suppressed because of many factors, such as the weak adsorption of fouling molecules on the respective electrode surface or the potential generation of strong oxidants (e.g., hydroxyl radicals) to suppress the formation of biofilm via self-cleaning. This review first considered the impact factors, such as surface chemistry (i.e., the doping levels, surface termination and crystal orientation) and surface topography, on the antifouling properties of BDDE. Investigation of the electrochemical fouling of a BDD surface and effective cleaning strategies to restore the activity of a BDD surface were then discussed. Next, recent progress and achievements regarding diamond sensors and biosensors for biologically-related sensing applications, particularly on the determination of fouling agents, were summarized, including representative antifouling applications, diamond microelectrodes, BDD-based microfluidic devices as well as noninvasive wearable sensors. The challenges and future of diamond for antifouling applications were finally discussed. Graphical abstract: Image 1